Optimal. Leaf size=29 \[ e^x+\frac {e^{2 (-3+x) x} \left (-e^{27 x^2}+x\right )^2}{x^4} \]
________________________________________________________________________________________
Rubi [B] time = 0.24, antiderivative size = 96, normalized size of antiderivative = 3.31, number of steps used = 6, number of rules used = 3, integrand size = 88, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.034, Rules used = {14, 2194, 2288} \begin {gather*} \frac {e^{-2 (3-28 x) x} \left (3 x-56 x^2\right )}{(3-56 x) x^5}-\frac {2 e^{29 x^2-6 x} \left (3 x-29 x^2\right )}{(3-29 x) x^4}+\frac {e^{-2 (3-x) x} \left (3 x-2 x^2\right )}{(3-2 x) x^3}+e^x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 14
Rule 2194
Rule 2288
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (e^x+\frac {2 e^{-6 x+29 x^2} \left (3+6 x-58 x^2\right )}{x^4}+\frac {2 e^{2 (-3+x) x} \left (-1-3 x+2 x^2\right )}{x^3}+\frac {2 e^{2 x (-3+28 x)} \left (-2-3 x+56 x^2\right )}{x^5}\right ) \, dx\\ &=2 \int \frac {e^{-6 x+29 x^2} \left (3+6 x-58 x^2\right )}{x^4} \, dx+2 \int \frac {e^{2 (-3+x) x} \left (-1-3 x+2 x^2\right )}{x^3} \, dx+2 \int \frac {e^{2 x (-3+28 x)} \left (-2-3 x+56 x^2\right )}{x^5} \, dx+\int e^x \, dx\\ &=e^x+\frac {e^{-2 (3-28 x) x} \left (3 x-56 x^2\right )}{(3-56 x) x^5}-\frac {2 e^{-6 x+29 x^2} \left (3 x-29 x^2\right )}{(3-29 x) x^4}+\frac {e^{-2 (3-x) x} \left (3 x-2 x^2\right )}{(3-2 x) x^3}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.05, size = 47, normalized size = 1.62 \begin {gather*} \frac {e^{-6 x} \left (e^{56 x^2}-2 e^{29 x^2} x+e^{2 x^2} x^2+e^{7 x} x^4\right )}{x^4} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.65, size = 48, normalized size = 1.66 \begin {gather*} \frac {x^{4} e^{x} + x^{2} e^{\left (2 \, x^{2} - 6 \, x\right )} - 2 \, x e^{\left (29 \, x^{2} - 6 \, x\right )} + e^{\left (56 \, x^{2} - 6 \, x\right )}}{x^{4}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.30, size = 48, normalized size = 1.66 \begin {gather*} \frac {x^{4} e^{x} + x^{2} e^{\left (2 \, x^{2} - 6 \, x\right )} - 2 \, x e^{\left (29 \, x^{2} - 6 \, x\right )} + e^{\left (56 \, x^{2} - 6 \, x\right )}}{x^{4}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.12, size = 41, normalized size = 1.41
method | result | size |
risch | \({\mathrm e}^{x}+\frac {{\mathrm e}^{2 x \left (28 x -3\right )}}{x^{4}}-\frac {2 \,{\mathrm e}^{x \left (29 x -6\right )}}{x^{3}}+\frac {{\mathrm e}^{2 x \left (x -3\right )}}{x^{2}}\) | \(41\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.61, size = 37, normalized size = 1.28 \begin {gather*} \frac {{\left (x^{2} e^{\left (2 \, x^{2}\right )} - 2 \, x e^{\left (29 \, x^{2}\right )} + e^{\left (56 \, x^{2}\right )}\right )} e^{\left (-6 \, x\right )}}{x^{4}} + e^{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.67, size = 46, normalized size = 1.59 \begin {gather*} {\mathrm {e}}^x+\frac {{\mathrm {e}}^{2\,x^2-6\,x}}{x^2}-\frac {2\,{\mathrm {e}}^{29\,x^2-6\,x}}{x^3}+\frac {{\mathrm {e}}^{56\,x^2-6\,x}}{x^4} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [B] time = 1.14, size = 68, normalized size = 2.34 \begin {gather*} e^{x} + \frac {\left (x^{7} e^{12 x} \left (e^{27 x^{2}}\right )^{\frac {2}{27}} - 2 x^{6} e^{12 x} \left (e^{27 x^{2}}\right )^{\frac {29}{27}} + x^{5} e^{12 x} \left (e^{27 x^{2}}\right )^{\frac {56}{27}}\right ) e^{- 18 x}}{x^{9}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________